Changes in Emotional Vitality as a Predictor of Levels and Change in Allostatic Load: Longitudinal Results From the Whitehall II Cohort Study. Issue 4 (May 2020) - Deen, Laura; Dich, Nadya; Head, Jenny; Clark, Alice Jessie
ABSTRACT: Objective: Increasing evidence has shown an association between reduced psychological well-being and long-term morbidity. However, longitudinal studies addressing potential biobehavioral mechanisms, such as physiological function, are lacking. The aim of this study is to examine the association between changes in emotional vitality on levels and changes in allostatic load (AL), a measure of multisystem physiological dysregulation, as well as its composite risk markers. Methods: Participants comprised 5919 British civil servants from phases 3, 5, and 7 of the Whitehall II study. Psychological well-being was operationalized as emotional vitality. AL was measured using nine biomarkers of the cardiovascular, metabolic, and immune system. Linear mixed-effect models were used to determine the association between changes in emotional vitality between phases 3 and 5 and subsequent levels and change in AL from phases 5 to 7. Generalized linear models were used to address the association between changes in emotional vitality and individual risk markers. Results: Increase in emotional vitality was associated with a lower mean level of AL, whereas the AL slope was not markedly affected. Among the included risk markers, only interleukin-6 was weakly associated with changes in emotional vitality, with a 7% reduced risk of high levels of interleukin-6 per one-unit increase in emotional vitality. Conclusion: This study found that an increase in emotional vitality was associated with subsequent lower levels, but not rate of change, of AL over time. Further research is needed to address the relationship between trajectories of psychological well-being and physiological dysregulation. Abstract : Supplemental digital content is available in the text.